Analisis Tabuhan Babun pada Iringan Tari Kuda Gipang di Sanggar Asam Rimbun Desa Pantai Hambawang Timur - Suwarjiya Suwarjiya; Gita Kinanthi Purnama Asri Adinda; Muhammad Mahmud (Mahesa Research Center, 2023)
The purpose of this study was to describe the pattern of the typical Baboon wasp/Banjar dialect to the accompaniment of the Kuda Gipang dance at the Asam Rimbun studio through sound study and notation. Qualitative descriptive research methods are used as a reference in implementing data collection techniques by interviewing, observing and documenting. The data that has been obtained is then analyzed to get the conclusion of the research findings in the form of the Banjar baboon notation. In this study, the Kuda Gipang Igal Anak dance was the sample. This activity lasts for 4-5 months. The results of the study are as follows: The Variety of Movements in the Kuda Gipang Dance at the Asam Rimbun Art Studio, is very much based on the rhythm of wasps of baboons. There are 11 distributions of wasp patterns based on the variety of motions, namely (1) Initial punch, (2) Timangan 1, (3) Timangan 2, (4) Kijik Punch, (5) Lagurih Punch, (6) Kapak Taguk Punch, (7) Punch Jumping Horse, (8) Horse Ax Punch, (9) Hunjal Punch, (10) Dump, (11) Sambah Dump. Baboons have Pambaduk and Rumpiang parts. There are 10 basic sound colors for baboons, 3 of which are produced by Pambaduk, 5 for Rumpiang and 2 for Pambaduk and Rumpiang Combined. Each pattern has 8 beats, using a 4/4 time scale, where there are 4 beats/counts in each bar -his. The. The baboon tabuhan in the Kuda Gipang Igal Anak dance has a role in harmony between the movements and the dance accompaniment and requires harmonization between the dancers and the musicians.